Review of studies concerning job performance of nursing staff - Szara, Marta; Ksykiewicz-Dorota, Anna; Klukow, Jadwiga; Lamont, Marzena (Nursing in the 21st Century, 2018)
REVIEW OF STUDIES CONCERNING JOB PERFORMANCE OF NURSING STAFF Introduction. Work performance is defined as a total value of behaviours expected from the employees during evaluation performed within a specified time. According to the basic and dichotomous division, performance refers to behaviours of employees (behavioural), and the results of their work. In addition, the researchers differentiate: task performance, contextual performance and adaptive performance. Results. Since the 1960s, many international researchers have been engaged in problems concerning the performance of work of nursing staff. Until today, the above-mentioned scope of problems remains up-to-date, but has been poorly recognized in Polish literature [1,2,3]. In the international reports the authors prove that the multi-aspect phenomenon of work performance depends on many variables. Many studies confirmed the relationship between job performance and personal traits of the employee, shift work, level of stress, social support, interpersonal relationships, leadership, as well as organizational culture.